2018
DOI: 10.1021/acs.jpcc.8b00835
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Zn and Mg Electrodeposition Mechanisms in Nonaqueous Electrolytes for Next-Generation Metal Batteries

Abstract: Cyclic voltammetry and linear sweep voltammetry with an ultramicroelectrode (UME) were employed to study Zn and Mg electrodeposition and the corresponding mechanistic pathways. CVs obtained at a Pt UME for Zn electroreduction from a trifluoromethylsulfonyl imide (TFSI − ) and chloridecontaining electrolyte in acetonitrile exhibit current densities that are scan rate independent, as expected for a simple electron transfer at a UME. However, CVs obtained from three different Mg-containing electrolytes in THF exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 57 publications
1
60
1
Order By: Relevance
“…The local maximum is likely representative of the initial magnesium nucleation. Because the electron transfer reaction is hypothesized to be preceded by a chemical equilibrium step (Ta et al, 2018), it is likely that the chemical equilibrium step causes the initial decrease in current for each electrolyte. The Cottrell equation could not be fit to either electrolyte; therefore, the Scharifker and Hill models for instantaneous and progressive nucleation could not be directly applied to this system (Scharifker and Hills, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…The local maximum is likely representative of the initial magnesium nucleation. Because the electron transfer reaction is hypothesized to be preceded by a chemical equilibrium step (Ta et al, 2018), it is likely that the chemical equilibrium step causes the initial decrease in current for each electrolyte. The Cottrell equation could not be fit to either electrolyte; therefore, the Scharifker and Hill models for instantaneous and progressive nucleation could not be directly applied to this system (Scharifker and Hills, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with a few separate studies that report on Zn full batteries using an AN-based electrolyte (116)(117)(118). It could also be attributable to the one-step, two-electron transfer mechanism of Zn as predicted by simulation (114), which results in a large reaction constant five orders of magnitudes larger than that of Mg electrodeposition from tetrahydrofuran that includes two steps. Together, the kinetics in the bulk (i.e., diffusivity) and at the interface (i.e., reaction constant) single out AN-based systems as a group of promising electrolytes for Zn batteries.…”
Section: Chemistry Of the Electrolyte And The Seimentioning
confidence: 94%
“…As illustrated in Fig. 4F, computation work suggests that Zn electrodeposition can proceed via a one-step, two-electron transfer mechanism in organic electrolyte, e.g., Zn(TFSI) 2 in acetonitrile (AN), which is comparatively faster than the kinetics of Mg, another HCP metal (114). Han et al (115) reported on a comprehensive experimental study of the electrochemical properties of nonaqueous Zn electrolytes including the combinations between one of the salts: Zn(TFSI) 2 , Zn(CF 3 SO 3 ) 2 , Zn(BF 4 ) 2 , Zn(PF 6 ) 2 , and one of the organic solvents: diglyme (G2), AN, propylene carbonate (PC), and N,N′-dimethylformamide (DMF).…”
Section: Chemistry Of the Electrolyte And The Seimentioning
confidence: 99%
“…Despite these desirable qualities, there are major challenges hindering the development of Mg batteries due to kinetic limitations associated with the transport and electrodeposition of the divalent cation. [ 13,14 ] While much progress has been made to increase the anodic stability and improve the efficiency of advanced Mg electrolytes, [ 15–17 ] the paucity of known cathode materials capable of reversible Mg 2+ (de)insertion continues to plague this technology. High voltage oxides generally suffer from sluggish Mg 2+ diffusion due to strong ionic interactions between the migrating cation and the highly polarizing lattice.…”
Section: Introductionmentioning
confidence: 99%